New records of bat flies (Diptera: Streblidae) in Oaxaca, Mexico - Liliana Tlapaya-Romero; Sergio Ibáñez-Bernal; Antonio Santos-Moreno (Revista Mexicana de Biodiversidad)
Species richness and parasitic prevalence of bat flies in a bat cave community in Oaxaca are reported. Between 2016 and 2018, a total of 732 bats were captured and inspected for streblids. We recorded 15 bat species from 3 families and obtained 1,317 streblid specimens corresponding to 24 species and 8 genera, including 19 species that are new records for the state: Nycterophilia fairchildi Wenzel, 1966, Nycterophilia parnelli Wenzel, 1966, Metelasmus pseudopterus Coquillett, 1907, Strebla guajiro (García & Casal, 1965), Strebla wiedemanni Kolenati, 1856, Aspidoptera phyllostomatis (Perty, 1833), Megistopoda aranea (Coquillett, 1899), Megistopoda proxima (Séguy, 1926), Paratrichobius longicrus (Miranda-Ribeiro, 1907), Trichobius brennani Wenzel, 1966, Trichobius diphyllae Wenzel, 1966, Trichobius galei Wenzel, 1966, Trichobius hoffmannae Guerrero & Morales-Malacara, 1996, Trichobius johnsonae Wenzel, 1966, Trichobius leionotus Wenzel, 1966, Trichobius sparsus Kessel, 1925, Trichobius sphaeronotus Jobling, 1939, Trichobius uniformis Curran, 1935, and Trichobius yunkeri Wenzel, 1966. Bat species with the highest parasite prevalence were Pteronotus parnellii (Gray, 1843), Desmodus rotundus (È. Geoffroy, 1810), and Artibeus jamaicensis Leach, 1821 with 88.1, 77.5, and 62.3%, respectively. After this study, the number of bat fly species known for the state of Oaxaca increases from 9 to 27, corresponding to 49% of the total Mexican streblid species richness.